Assessment of magnetic resonance velocity mapping of global ventricular function during dobutamine infusion in coronary artery disease. Issue 2 (August 1995) - Pennell, D. J.; Firmin, D. N.; Burger, P.; Yang, G. Z.; Manzara, C. C.; Ell, P. J.; Swanton, R. H.; Walker, J. M.; Underwood, S. R.; Longmore, D. B.
Abstract : BACKGROUND–Magnetic resonance imaging (MRI) is a versatile technique for examination of the cardiovascular system but only recently has assessment of myocardial ischaemia in coronary artery disease (CAD) become possible, for example by demonstrating abnormalities of regional ventricular contraction during stress. Global ventricular function during stress was assessed by MRI of aortic flow, which has not been previously attempted. DESIGN–Variables measured by MRI reflecting the effect of ischaemia on global ventricular function during dobutamine stress were correlated with thallium-201 myocardial perfusion tomography. PATIENTS–10 normal controls and 25 patients with CAD. SETTING–Tertiary cardiac referral centre. METHODS–Novel MRI sequences and analysis systems were used to measure the following variables during staged dobutamine infusion to 20 micrograms/kg/min: stroke volume, cardiac output, cardiac power output, peak flow, peak flow acceleration, aortic back flow, and flow wave velocity. Heart rate, blood pressure, double product, and maximum tolerated dobutamine dose were also measured. Multiple regression analysis was used to compare changes during stress with 201TI tomography. RESULTS–All parameters except for stroke volume and diastolic blood pressure increased in the controls. In the patients with CAD a significant relation was shown between the extent of reversible ischaemia and the change in peak flow acceleration (P < 0.00001), peak flow (P = 0.002), cardiac power output (P = 0.036), maximum dobutamine dose (P = 0.039), and systolic blood pressure (P = 0.04). Peak flow acceleration accounted for 58.4% of the variation in reversible ischaemia, and after allowing for this, only cardiac power output remained independently predictive adding a further 4.2% to the model (adjusted r2 = 0.626). A decrease in peak flow acceleration with an increase in dobutamine infusion indicated moderate or severe ischaemia (chi 2 = 10.2, P = 0.017). CONCLUSION–MRI may be used to assess variables of aortic flow during stress, which includes acceleration with high temporal resolution. Peak flow acceleration was the most sensitive indicator of the effect of ischaemia on global ventricular function.